Can existing policies inform adaptation tracking? - Nowak, Andreea C.; Njuguna, Lucy; Crumpler, Krystal; Rosenstock, Todd S. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Poster presented at the Adaptation Futures Conference (Montreal, October 2023). The poster summarizes work on reviewing 53 NDCs and 12 NAPs of African countries. Key messages: Evidence on adaptation processes and effects is required to improve investments in adaptation. Adaptation tracking systems need to respond to contextual needs and resources, in order to be used effectively. We assess if and how existing policies can facilitate adaptation tracking. We establish six elements that provide comprehensive information across the adaptation cycle: hazards, systems at risk, goals, objectives, actions, and indicators. We ask: Do policies include comprehensive and robust information on the six elements to ensure effective tracking? We provide insights into how adaptation tracking can leverage existing systems to ensure a country-driven process. We contribute to discussions on the Global Goal on Adaptation (GGA) and on improving national efforts to assess adaptation.